(untitled) - Urman, Scott (Berkeley, Calif., 2000)
This latest edition of Scott Urman's definitive guide to PL/SQL programming under Oracle databases, Oracle8i Advanced PL/SQL Programming, takes into account the new features of the language under Oracle 8i. Urman cut out some of the introductory PL/SQL material that appears in his earlier Oracle works, letting him focus more fully on higher-level aspects of the language and advanced techniques for putting them to use. Still, quite a bit of introductory material--including information on PL/SQL development environments--appears here, so don't be afraid to dive into Oracle 8i PL/SQL with this book if you can afford to buy only one guide.
Keywords: Oracle (Computer file),PL/SQL (Computer program language)